THE TORTOISE & THE HARE - Pitts , Sorrel (Penguin Random House UK - Ladybird, 2016)
Hare can run and jump. Tortoise can walk. Hare and Tortoise have a race, but can Tortoise win? Hare is fast and he is slow!